Numerical simulation of shear-strengthening of reinforced concrete beams by CFRP under cyclic loading - Shahbazpanahi, Shahriar; Hama Ali, Hunar Farid (Revista de la Construcción. Journal of Construction, 2019)
A novel finite element model is proposed to simulate reinforced concrete (RC) beams strengthened in shear by carbon fibre-reinforced polymer (CFRP) plate under cyclic loading. A spring element is developed to simulate the fracture zone based on the virtual crack in the sub-concrete material. The mass and damping matrix of the spring element is defined to model crack propagation in the sub-concrete material on nonlinear fracture mechanics under cyclic loading. A new energy release rates is computed to compare to the critical energy release rate of the sub-concrete material. A bar element is set parallel to the spring element to model the effect of the CFRP strengthened in shear and to calculate the energy dissipation rate by the CFRP based on virtual crack. The mass and damping matrix of the bar element is defined as well. When the finite element model is performed, the energy release rates can be computed simultaneously. Crack propagation can be studied with the implementation of new fracture criterion. The results of the proposed model are compared with the conventional fracture models carried out by commercial ABAQUS software based on linear elastic fracture mechanics and the previous experimental tests data. The results from the proposed model are in reasonable agreement with the results of previous experimental test.